NON-MOTOR SYMPTOMS OF PARKINSON DISEASE - N.A. ZARIPOV; J.S. DODKHOEV; S.M. ABDULLOZODA; R.J. JAMOLOVA (Avicenna Tajik State Medical University, 2021)
Objective: To assess the specific non-motor symptoms of Parkinson disease (PD) at its early (preclinical) stages using the NMSQuest scale. Methods: The respondents were divided into 2 groups. The first (main) group included 43 patients with confirmed PD at the age of 51-79 years, on average 66.18±7.79 years. PD duration in the main group ranged from 7 to 28 years (12.65±4.86). The following forms of PD were identified: mixed form - 28 patients (65.1%), akinetic-rigid form - 9 patients (20.9%) and trembling form - 6 patients (13.9%). The second group (control) included 28 individuals without signs of neurodegenerative diseases, including PD, and other severe somatic pathologies. Their age ranged from 47 to 81 years (64.75±10.05). The following concomitant disorders (initial stages, compensated forms) were found in the patients of the 2nd group: arterial hypertension - in 13 patients (46.4%), diabetes mellitus - 9 patients (32.1%); osteoarthritis - 6 patients (21.4%). Results: Non-motor signs of PD, such as hypersalivation, decreased sense of smell, difficulty swallowing, memory impairment, constipation, increased sweating, difficulty walking and loss of self-confidence were significantly more often noticed in the main group, which indicated that they were typical for the patients with PD. It can be assumed that these symptoms could predict the development of PD during the latent and prodromal periods of the disease. Conclusion: Undoubtedly, the motor symptoms that occur in PD exert a significant negative affect on the lifestyle of patients. However, the non-motor symptoms of the disease should not be overlooked. Although many scientists associate the non-motor symptoms of PD with the aging process, our study showed that the use of screening scales confirmed their specificity for PD and correlation with its duration. At the same time, statistical analysis showed that a number of symptoms are characteristic only of PD, while the rest are associated with the natural aging process.